Elementary School Principals' Learning Leadership and Innovative Behavior in Using School-Based Management - Jumaria Sirait; Osco Parmonangan Siajabat; Selviana Napitupulu; Fajar Ningsih Simanjuntak; Yoel Octobe Purba (AL-ISHLAH: Jurnal Pendidikan, 2022)
The study aimed to determine the effect of principals' learning leadership and innovative behaviour in implementing School-Based Management in SD Negeri Dolok Pardamean District, Simalungun Regency in 2021. This type of research was explanatory, so the appropriate method used was the survey method of 15 school principals as research respondents. The research instrument is a questionnaire containing 25 positive and negative statements with five answer choices located on a continuum line according to the Likert scale model and in the form of a closed questionnaire. Before being used, the questionnaire has been tested, and the results can be used as a research instrument. Data analysis techniques include descriptive analysis, requirements analysis tests, and hypothesis testing. Descriptive analysis was conducted to obtain an overview of the data from each research variable which was shown through the mean, median, mode, frequency distribution, and graphs. To identify the trend of each research variable, the average ideal score (Mi) and the ideal standard deviation (SDi) were used. Supported by the very strong learning leadership and innovative behaviour of the primary school principal; (3) Based on hypothesis testing, the results of the calculation of the value of th tt at a significance level of 0.05 are 5.96 2.02. The conclusion that there is a significant influence on learning leadership and innovative behaviour of elementary school principals in implementing School-Based Management is accepted as true.